Navigating AI Implementation in Local Government : Addressing Dilemmas by Fostering Mutuality and Meaningfulness - Heinisuo, Emmi; Kuoppakangas, Päivikki; Stenvall, Jari (Springer Science and Business Media, 2025)
This study explores AI-enabled local public service provisioning, especially dilemmas of the mutual and meaningful development process. Theoretically, it builds on the current literature on AI implementation in the public sector and relates it to the theorisations of mutuality and meaningfulness. Empirically, it examines the experiences of public agents in a qualitative case study of chatbot development by the City of Oulu, Finland. The study concludes six factors that are constructed into three interconnected dilemma pairs to examine cross-cutting problematic decision-making scenarios and provide reconciliations through mutuality and meaningfulness.